Indexing clinical documents for long-term preservation through an international coding system - Erika Pasceri; Maria Teresa Chiaravalloti (JLIS.it)
This paper describes the experience of mapping the document types defined by Medas company, a Digital Preservation Organization for healthcare institutions, to the Logical Observation Identifiers Names and Codes (LOINC) international standard, and consequently assess its adequacy in representing specificities of the Italian context. Mapping operations were manually performed by LOINC Italia experts. The LOINC database was searched using the LOINC Search web browser and REgenstrief LOINC Mapping Assistant (RELMA) software, employing local names and synonyms of Medas document types. Out of 483 Medas document types, 144 fully match with a LOINC code; 211 were associated to a LOINC code which only partially covers the meaning; 128 are not covered by LOINC. Although the axes of LOINC Document Ontology are quite adequate for document types representation, an extension of Kind of document and Subject Matter Domain axes is desirable. Local Medas codes reflects the variety of clinical document types produced in the Italian healthcare domain and the results of this case study can be used as new terms submissions to enrich the LOINC standard, especially in relation to the specificities that characterize the Italian national context.